Role of perioperative nutritional status and enteral nutrition in predicting and preventing post-operative complications in patients with Crohn’s disease - Jiang, Tianyu; Jiang, Yongmei; Jin, Qianwen; Xu, Shining; Fingerhut, Abraham; Shi, Yongmei; Zheng, Minhua; He, Zirui (Frontiers in Nutrition, 2023)
Background Perioperative immune-nutritional status is correlated with post-operative outcomes. This study aimed to evaluate whether pre-operative nutritional status could predict post-operative complications in patients with Crohn’s disease (CD) and whether pre-operative enteral nutrition (EN) can prevent post-operative complications. Methods This retrospective cohort study analyzed the electronic health records of 173 patients diagnosed with CD in Ruijin Hospital, Shanghai, China, between August 2015 and May 2021: 122 patients had pre-operative nutritional support while 51 patients underwent surgery without pre-operative nutritional support. The pre-operative nutritional status, disease activity index, disease-related data, frequency of multiple surgery, operative data, and post-operative characters in each group were compared to determine whether the nutritional support and status could significantly affect post-operative outcome. One-to-one propensity score matching (PSM) was performed to limit demographic inequalities between the two groups. Results After PSM, no statistically significant differences were found in pre-operative patient basic characteristics between the two groups of 47 patients (98 patients in all) included in this study. Overall, 21 patients developed 26 post-operative complications. In terms of pre-operative nutritional status, the level of serum albumin (ALB), pre-albumin (pre-ALB), and hemoglobin (Hb) in the nutrition group were statistically higher than that in the control group. We also observed a statistically significant decrease in post-operative complications, need for emergency surgery, and staged operations, while the rate of laparoscopic surgery was higher in the nutrition group compared to the non-nutritional group. Post-operative complications were related to pre-operative nutritional condition, which indicated that EN may improve the nutritional status and reduced the rate of post-operative complications. Conclusion Pre-operative nutritional status is correlated with post-operative outcomes while EN plays a positive role in preventing the post-operative complications. EN is useful for improving the pre-operative nutritional status and reducing the post-operative adverse events for CD patients undergoing surgery.